Soluble HLA-G and TGF-β in couples attending assisted reproduction – A possible role of TGF-β isoforms in semen?. (February 2020) - Nilsson, Line Lynge; Hornstrup, Micha B.; Perin, Trine L.; Lindhard, Anette; Funck, Tina; Bjerrum, Poul J.; Mule, Henriette Theilmann; Scheike, Thomas; Nielsen, Henriette Svarre; Hviid, Thomas Vauvert F.
Highlights: Significant associations between semen sHLA-G levels and HLA-G gene variations. TGF-β2 levels in semen are lower in sperm donors compared to infertility patients. TGF-β3 levels in semen are higher in sperm donors compared to infertility patients. Abstract: Soluble isoforms of the non-classical Human Leukocyte Antigen (HLA)-G as well as Transforming Growth Factor (TGF)-β is expressed in seminal plasma possibly influencing the pregnancy potential. We wanted to examine the association of seminal plasma sHLA-G, TGF-β1, TGF-β2 and TGFβ3 with pregnancy success in a cohort of 127 couples and 4 single women attending fertility treatment with the use of assisted reproduction technologies (ART). Soluble HLA-G, TGF-β1, TGF-β2 and TGF-β3 in seminal plasma did not fluctuate significantly over time. We did not find any impact of seminal plasma sHLA-G, TGF-β1, TGF-β2 and TGF-β3 on time-to-pregnancy measured as number of treatment cycles. There was a significant association between concentrations of seminal plasma sHLA-G and HLA-G variations in the 3'untranslated region (3'UTR) of the HLA-G gene, supporting and extending previous findings. Furthermore, by comparing seminal plasma concentrations of sHLA-G, TGF-β1, TGF-β2 and TGF-β3 in male subjects with reduced semen quality, male subjects with normal semen quality, and sperm donors, we found that TGF-β2 was significantly lower, and TGF-β3 was significantly higher, in seminal plasma from sperm donors. These findings suggest that TGF-β isoforms may influence semen quality and fertility.